Evaluation of Physical Education In SLB-C of South Kalimantan Province - Imam Yuwono (Universitas Bengkulu, 2021)
This study aims to determine the level of success of learning in Physical Education, Sports and Health (Physical Education) class IX 2018/2019 academic year at SLB-C of South Kalimantan Province and to produce recommendations for decision makers to follow up on the ongoing learning program. The evaluation model used in this research is the CIPP evaluation model using descriptive statistical analysis techniques with percentages. This technique is used to analyze data obtained from the results of distributing questionnaires, and uses a model developed by (Daniel Stufflebeam, 2014), namely (1) context, (2) input, (3) process, and (4) product or what is called CIPP. Data were collected from observations, questionnaires, and documentation studies. The results of this study indicate that the overall variable of SLB-C of South Kalimantan Province gets a percentage of 70.5% with good criteria. Based on the results of these data, it can be decided that overall educational learning in the State Special School Guidance for South Kalimantan Province is in good criteria. Recommendations based on the results of this study are to continue the learning program, but accompanied by revisions to several variables.